Olympia, Griechenland. Die Geschichte der Ausgrabung in der III. und IV. Kampagne. Eine digitale Rekonstruktion in iDAI.field. Die Arbeiten des Jahres 2021 - Zielke, Kristina (e-Forschungsberichte des DAI, 2022)
The project »Olympia – Die Geschichte der Ausgrabung in der III. und IV. Kampagne« is part of a large-scale research project, which aims to digitally reconstruct the early excavations at Olympia. The main emphasis of the DAI’s research fellowship was the third and fourth campaign of the so-called Alte Grabung, that took place between 1877 and 1879. Based on digital copies of the archival material, the project aimed at reconstructing the excavations and their progress over the course of time and to allot the reconstructed sections with additional information regarding finds and their context.